Village Fund Allocation and Village Welfare: The Role of Village Potential as a Moderator - Tehupuring, Ronald (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Village fund allocation remains a significant concern for the government due to persistent cases of misuse that can reduce village welfare. The purpose of this study is to examine and analyze the effect of village fund allocation on village welfare, moderated by village potential. This study used a purposive sampling method for all provincial governments in Indonesia that reported village financial data for 2017-2020. The analytical approach used panel data regression with eViews version 12. The study found that village fund allocation had a positive and significant effect on village welfare. However, village potential did not significantly enhance the effect of village fund allocation on village welfare. The practical implication of this study is that village fund allocation has been proven to significantly improve village welfare, making it crucial to ensure optimal distribution and management. Furthermore, this study explains that village potential has not been able to moderate the effect of village funds, indicating that this potential may not be optimally utilized. Therefore, efforts are needed to strengthen village capacity to manage existing potential to achieve synergy between village funds and local potential. This study can also serve as a reference for local governments in designing local potential-based development strategies that are more integrated with village funding.